Designing a Research Proposal for Construction Materials Health Management (CMHM) System - Redmond, Alan Martin; Fies, Bruno; Zarli, Alain (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
This papers problem statement relates to IAQ and the sharp rise in the number of people diagnosed with allergic diseases in developed countries. The issues of customizing homes for health needs of their occupants requires proofing against allergens caused by materials or products. In order, to use ICT applications systems for identifying/analyzing materials between customers and suppliers, an inter-organizational system is required. However, such a process has limitations due to dependencies on different data structures between all interfaces and an external system. The papers methodology is based on purposing ‘CRM - BI - SCM’ interface system that will ensure compatibility between system segments and components of CMHM system. The system architecture features; i) knowledge-based support system (TOPIS method) for evaluation of hazardous material selection; ii) linking BIM (Building Information Model) model components with a materials selection that not only prompts the cost per unit but also predicts the potential hazards associated with this decision; and iii) OWL-S specification for atomic process focusing on semantic match making. The proposal presents an interface based on Cloud BIM platform as an integrated information system that links material components that are tagged to health documents extracted from a BIM model in order to provide an online supply Network of the whole Business Process.